2001
DOI: 10.1046/j.1523-1755.2001.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hypertension in chronic hemodialysis patients

Abstract: HD unit BP values can be used to identify the presence or absence of hypertension, although prediction of ambulatory BPs from HD unit BP values cannot be made reliably in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 22 publications
5
70
2
3
Order By: Relevance
“…coefficients for agreement between 44-h interdialytic ABP and pre/postdialysis BP ranged from 0.32 to 0.60, indicating fair to moderate agreement (30). Similarly, Agarwal and Lewis (29) reported that a 2-wk averaged predialysis BP of Ͼ150/85 mmHg or a postdialysis BP of Ͼ130/75 mmHg had at least 80% sensitivity in diagnosing hypertension but had poor specificity. The combined analyses (Bland-Altman plots) clearly show that the agreement between pre/postdialysis BP and ABPM is poor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…coefficients for agreement between 44-h interdialytic ABP and pre/postdialysis BP ranged from 0.32 to 0.60, indicating fair to moderate agreement (30). Similarly, Agarwal and Lewis (29) reported that a 2-wk averaged predialysis BP of Ͼ150/85 mmHg or a postdialysis BP of Ͼ130/75 mmHg had at least 80% sensitivity in diagnosing hypertension but had poor specificity. The combined analyses (Bland-Altman plots) clearly show that the agreement between pre/postdialysis BP and ABPM is poor.…”
Section: Discussionmentioning
confidence: 95%
“…We believe that self-recorded BP (home) monitoring is a promising technique that, via involvement of patients in the delivery of their health care, may improve BP management. Although we could not pool the results of various studies by meta-analysis, it seems that dialysis unit BP still may be useful in a qualitative sense (29). …”
Section: Discussionmentioning
confidence: 97%
“…However, most investigators have taken 2-week averaged predialysis or postdialysis BP measurements when they have compared these to ambulatory recordings (15,16). What remains unknown is the diagnostic performance of BP recording obtained just before or just after dialysis on a single occasion.…”
mentioning
confidence: 99%
“…Consequently, diagnosis and treatment of BP in PCHD must be considered in respect of pre/postdialysis MAP and especially PP values, not just depending on pre/postdialysis systolic and diastolic pressure values. 36,37 Furthermore, epidemiological studies of mortality and morbidity of PCHD must be consequently revised. Differences in MAPs and PPs could be helpful in the explanation of the 'paradox' of increasing mortality in PCHD with lower BP levels.…”
Section: Discussionmentioning
confidence: 99%